From Pasir Ris to Pioneer: Singapore’s mass rapid transit (MRT) station names in relation to its identity - Lim, Shaun Tyan Gin (2023)
This article examines the station names of 142 Mass Rapid Transit (MRT) stations across Singapore’s five fully operational MRT lines using primary sources (digitised newspapers, maps, and press releases) and secondary sources (scholarly research on Singapore place names and information from government agencies). There are two research objectives: firstly, to determine the common naming strategies of Singapore’s MRT station names, and secondly, to analyse features of Singapore’s socio-political and linguistic identity by studying these names. Common naming patterns of Singapore’s station names include associative names, where the station is named after nearby physical or man-made features; descriptive names, where the name describes a particular aspect of the area; and eponymous names, where the station is named after a famous person or entity. We argue that station names reflect the state’s language and socio-political policies and shed deeper light on some of the complex and contradictory forces at play in the nation’s linguistic and socio-political identity. Singapore’s language shift towards English is evident as English is frequently used to name stations, particularly among newer MRT lines, where the public can suggest and vote on station names. At the same time, there are toponyms in local languages like Malay that serve as indexes of localness of the area around the station, showing the cultural dimension that station names have as metaphors for the area’s history and heritage. Yet, Singapore’s pragmatic socio-political identity ultimately means that the practical, referential function of names takes precedence over the cultural functions of naming.